Transforming social norms to end FGM in the EU: an evaluation of the REPLACE Approach - Barrett, Hazel Rose; Brown, Katherine; Alhassan, Yussif; Leye, Els (Reproductive health, 2020)
Background Despite numerous campaigns and interventions to end female genital mutilation (FGM), the practice persists across the world, including the European Union (EU). Previous interventions have focused mainly on awareness raising and legislation aimed at criminalizing the practice. Limited evidence exists on the effectiveness of interventions due in part to the lack of systematic evaluation of projects. This paper presents an evaluation of the REPLACE Approach, which is a new methodology for tackling FGM based on community-based behaviour change and intervention evaluation. Methods We developed, trialed and evaluated the REPLACE Approach through extensive engagement with eight FGM affected African diaspora communities in five EU countries. We employed qualitative and quantitative tools to obtain data to inform the development, implementation and evaluation of the Approach. These included community-based participatory action research, questionnaires and community readiness assessments. The research took place between 2010 and 2016. Results Findings suggested that the Approach has the capability for building the capacities of FGM affected communities to overturn social norms that perpetuate the practice. We observed that community-based action research is a useful methodology for collecting data in FGM intervention settings as it allows for effective community engagement to identify, educate and motivate influential community members to challenge the practice, as well as obtaining useful information on the beliefs and norms that shape the practice. We also found that community readiness assessments, pre and post intervention, were useful for tailoring interventions appropriately and for evaluating changes in attitudes and behaviour that may have resulted from the interventions. Conclusion This evaluation has demonstrated that the REPLACE Approach has the potential, over time, to bring about changes in norms and attitudes associated with FGM. Its strengths lay in the engagement with influential community members, in building the capacity and motivation of community members to undertake change, in recognising contextual differences in the barriers and enablers of FGM practice and in tailoring interventions to local community readiness to change, and then evaluating interventions to re-inform implementation. The next steps would therefore be to implement the Approach over a longer time frame to assess if it results in measurable change in behaviour.